Cardiac involvement in a cross‐sectional cohort of myotonic dystrophies and other skeletal myopathies. (31st May 2020) - Schmid, Johannes; Beer, Meinrad; Berghold, Andrea; Stojakovic, Tatjana; Scharnagl, Hubert; Dieplinger, Benjamin; Quasthoff, Stefan; Binder, Josepha S.; Rainer, Peter P.
Abstract: Aims: Cardiac involvement in myopathies that primarily affect the skeletal muscle is variable and may be subtle, necessitating sensitive diagnostic approaches. Here, we describe the prevalence of cardiac abnormalities in a cohort of patients with skeletal muscle disease presenting at a tertiary care neuromuscular centre. Methods and results: We systematically investigated patients with skeletal myopathies and comprehensively analysed their cardiac phenotype including 24 h electrocardiogram, echocardiography with strain analyses, contrast‐enhanced cardiac magnetic resonance imaging, and, if at increased risk of coronary artery disease, computed tomography coronary angiography. We prospectively screened 91 patients with diverse skeletal myopathies and enrolled 73 patients. The most pronounced cardiac involvement was present in patients with dystrophic myopathies (cardiac abnormalities in 59% of patients). We analysed myotonic dystrophies ( n  = 29) in more detail and found prolonged QRS (99.4 ± 15.6 vs. 91.5 ± 10.3 ms; P  = 0.027) and QTc times (441.1 ± 28.1 vs. 413.0 ± 23.3 ms; P  < 0.001) and increased left atrial size (27.28 ± 3.9 vs. 25.0 ± 3.2 mm/m 2 ; P  = 0.021) when compared with healthy controls. Left ventricular systolic function was reduced (ejection fraction < 55%) in 31% of myotonic dystrophies, while only 4% had an ejection fraction < 50%. Apical peak systolic longitudinal strain was slightly reduced ( P  = 0.023). Conclusions: Screening for cardiac involvement in the skeletal muscle disease seems prudent particularly in patients with dystrophic myopathies. In the subset of myotonic dystrophy patients, QRS and QTc times as well as myocardial strain may be useful parameters. Their potential for predicting cardiac adverse events needs further evaluation.